Ropinirole suppresses LPS-induced periodontal inflammation by inhibiting the NAT10 in an ac4C-dependent manner - Haiqing Liao; Huabing Ma; Hongying Meng; Na Kang; Lufei Wang (BMC, 2024)
Abstract Background Periodontitis is a chronic osteolytic inflammatory disease, where anti-inflammatory intervention is critical for restricting periodontal damage and regenerating alveolar bone. Ropinirole, a dopamine D2 receptor agonist, has previously shown therapeutic potential for periodontitis but the underlying mechanism is still unclear. Methods Human gingival fibroblasts (HGFs) treated with LPS were considered to mimic periodontitis in vitro. The dosage of Ropinirole was selected through the cell viability of HGFs evaluation. The protective effects of Ropinirole on HGFs were evaluated by detecting cell viability, cell apoptosis, and pro-inflammatory factor levels. The molecular docking between NAT10 and Ropinirole was performed. The interaction relationship between NAT10 and KLF6 was verified by ac4C Acetylated RNA Immunoprecipitation followed by qPCR (acRIP-qPCR) and dual-luciferase reporter assay. Results Ropinirole alleviates LPS-induced damage of HGFs by promoting cell viability, inhibiting cell apoptosis and the levels of IL-1β, IL-18, and TNF-α. Overexpression of NAT10 weakens the effects of Ropinirole on protecting HGFs. Meanwhile, NAT10-mediated ac4C RNA acetylation promotes KLF6 mRNA stability. Upregulation of KLF6 reversed the effects of NAT10 inhibition on HGFs. Conclusions Taken together, Ropinirole protected HGFs through inhibiting the NAT10 ac4C RNA acetylation to decrease the KLF6 mRNA stability from LPS injury. The discovery of this pharmacological and molecular mechanism of Ropinirole further strengthens its therapeutic potential for periodontitis.